Bioanalisis Toksisitas Air Tanah Di Sekitar Tpa Sampah Menggunakan Biji Kacang Hijau (Vigna Radiata) Sebagai Penanda Stres Oksidatif - Saepudin Rahmatullah; Anggita Yuli Amalia; Devita Anggraeni Putri; Fitrah Nur Hanifah; Muhammad Akbar Jiddan; Putri Afdhilani Nur Saadah (Jurnal Multidisiplin Dehasen (MUDE), 2026)
Leachate from landfills (TPS/TFA) has the potential to contaminate surrounding groundwater with various toxic compounds. This study aims to evaluate the toxicity of groundwater around the landfill on germination and oxidative stress responses in mung bean (Vigna radiata) sprouts. Groundwater samples were taken at distances of 10, 40, 100, and 300 meters from the landfill. The sprouts were planted on cotton media moistened with groundwater samples at 100% (original) concentration and observed for 72 hours. Parameters observed included germination percentage, radicle and hypocotyl length, and catalase (CAT) enzyme activity as an indicator of oxidative stress. The results showed that all seeds germinated (100%), but radicle and hypocotyl growth was significantly inhibited as the distance between the samples and the landfill increased. Catalase enzyme activity increased sharply in sprouts exposed to groundwater from the closest distance (10 m), approximately 9.5 times higher than in the control (distilled water). This increase in catalase activity indicates oxidative stress induced by pollutant compounds in the groundwater. The results demonstrate that mung beans can function as a sensitive bioindicator for detecting toxicity and oxidative stress caused by groundwater pollution around landfills. Measurement of catalase enzyme activity provides information on sublethal impacts not apparent from germination parameters alone.